2014
DOI: 10.3928/01913913-20141021-06
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Membrane for Reducing the Formation of Adhesions in Strabismus Surgery: Experimental Study in Rabbits

Abstract: Human amniotic membrane in rabbits led to an increase in the inflammatory process and a decrease in fibrosis formation following strabismus surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…These data suggested that cryopreserved AM did not improve the recovery of the active muscle properties. The significant muscle stress reduction showed at 30 days AM could be related to the increase of inflammation provoked by the membrane, previously described by different authors (12,20,28,29). This phenomenon, related to the xenogenic nature of the equine AM, would reverse the anti-inflammation effect of the membrane, slowing down the muscle active properties recovery.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…These data suggested that cryopreserved AM did not improve the recovery of the active muscle properties. The significant muscle stress reduction showed at 30 days AM could be related to the increase of inflammation provoked by the membrane, previously described by different authors (12,20,28,29). This phenomenon, related to the xenogenic nature of the equine AM, would reverse the anti-inflammation effect of the membrane, slowing down the muscle active properties recovery.…”
Section: Discussionmentioning
confidence: 51%
“…The use of cryopreserved amniotic membrane after strabismus surgery has been deeply studied in the literature (9,10,12,17). Among their main effects, AM reduces the tissue inflammation, neovascularization and scar formation of the muscle resected or recessed (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of such agents should be regarded with caution as they may also decrease the reattachment of the extraocular muscle to the scleral tissue. The role of amniotic membrane to reduce postoperative scarring is studied by different groups and conflicting results are reported about the effect of reducing postoperative scarring161718192021222324.…”
Section: Treatmentmentioning
confidence: 99%